Genomic differentiation of Deschampsia antarctica and D. cespitosa (Poaceae) based on satellite DNA - González, María Laura; Chiapella, Jorge Oscar; Topalian, Juliana; Urdampilleta, Juan Domingo (Botanical Journal of the Linnean Society)
Repetitive DNA is a rapidly evolving component of vascular plant genomes, which can account for genomic differentiation in plant lineages. Satellite DNA (satDNA) is tandem repetitive DNA for which array size and disposition on chromosomes may vary between reproductively isolated groups, such as different populations or closely related species. Deschampsia is a cosmopolitan grass genus growing in temperate and cold regions; D. cespitosa is widespread all over the world, whereas D. antarctica is restricted to Antarctica and southern Patagonia. The present work aims to the identification, isolation and comparison of satDNA from the genomes of two Deschampsia spp. with bioinformatics tools and their subsequent analysis and cytological study. The genomic analysis of TAREAN found 34 families of satDNA included on 21 superfamilies, most of them shared between the two species. Some of these satDNAs presented homology with others previously reported for grasses. A few satDNA families were found exclusively in one of the species. Most satDNAs were found in both species and showed high sequence homology, but their distribution on chromosomes was different between species. This highlights the importance of changes in the genomic disposition of satDNA in the evolution of species. Based on the 'satDNA library hypothesis' the differential amplification of satDNAs between independent lineages may be the cause of such differences. Fil: González, María Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto Multidisciplinario de Biología Vegetal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto Multidisciplinario de Biología Vegetal; Argentina Fil: Chiapella, Jorge Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto Multidisciplinario de Biología Vegetal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. ...